Colônias e responsabilidade moral - Du Bois, W. E. B.; Oliveira (tradução), Maurício da Costa (Afro-Ásia, 2024)
Tradução de: W. E. B. Du Bois, "Colonies and moral responsibility", in The Journal of Negro Education , Summer, 1946, Vol. 15, No. 3, The Problem of Education in Dependent Territories (Summer, 1946), pp. 311-318.